Awareness of cervical cancer and screening in Benin and Cameroon: an analysis of the Demographic and Health Survey, 2017-2018 - Nike A Olajide; Bhautesh D Jani; Claire L Niedzwiedz; Cathy Johnman; Kathryn A Robb (Journal of Global Health Reports)
# Background